2020
DOI: 10.1021/acs.jmedchem.0c01924
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Tetrahydroquinoline Inhibitors of NLRP3 Inflammasome for Potential Treatment of DSS-Induced Mouse Colitis

Abstract: The NLRP3 inflammasome is a critical component of innate immunity, which defends internal and external threats. However, inappropriate activation of the NLRP3 inflammasome induces various human diseases. In this study, we discovered and synthesized a series of tetrahydroquinoline inhibitors of NLRP3 inflammasome. Among these analogues, compound 6 exhibited optimal NLRP3 inhibitory activity. In vitro studies indicated that compound 6 directly bound to the NACHT domain of NLRP3 but not to protein pyrin domain (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 69 publications
0
41
0
Order By: Relevance
“…Other compounds have been shown to be effective for the treatment of DSS-induced experimental colitis in mice. A novel tetrahydroquinoline inhibitor of NLRP3, compound 6, specifically inhibits NLRP3 activation in vivo and attenuates colitis severity in the DSS mouse model [ 167 ] by directly binding to the NACHT domain of NLRP3, inhibiting its ATPase activity and blocking ASC oligomerization [ 167 ]. 1-Ethyl-5-methyl-2-phenyl-1H-benzo[d]imidazole, a synthetic small molecular compound also named Fc11a-2, was shown to induce beneficial effects in the treatment of DSS-induced experimental colitis in mice by targeting the NLRP3 inflammasome and inhibiting cytokine release [ 168 ].…”
Section: Nlrp3 Inflammasome As a Promising Target For Cancer Therapymentioning
confidence: 99%
“…Other compounds have been shown to be effective for the treatment of DSS-induced experimental colitis in mice. A novel tetrahydroquinoline inhibitor of NLRP3, compound 6, specifically inhibits NLRP3 activation in vivo and attenuates colitis severity in the DSS mouse model [ 167 ] by directly binding to the NACHT domain of NLRP3, inhibiting its ATPase activity and blocking ASC oligomerization [ 167 ]. 1-Ethyl-5-methyl-2-phenyl-1H-benzo[d]imidazole, a synthetic small molecular compound also named Fc11a-2, was shown to induce beneficial effects in the treatment of DSS-induced experimental colitis in mice by targeting the NLRP3 inflammasome and inhibiting cytokine release [ 168 ].…”
Section: Nlrp3 Inflammasome As a Promising Target For Cancer Therapymentioning
confidence: 99%
“…Numerous of drug studies have observed that inhibition of the upstream NLRP3 inflammasome pathway and IL-1β has a protective effect on NLRP3 inflammasome-mediated diseases, but these drugs are less specific and may evade the target. Currently available clinical therapies for NLRP3-associated diseases include drugs that target IL-1β, such as the recombinant IL-1 receptor antagonist anakinra, the neutralising IL-1β antibody canakinumab, and the soluble decoy IL-1β receptor lilonapil ( Jiang et al., 2017 ; Dai et al., 2021 ). However, the suppression of NLRP3 expression is more efficient and economical.…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%
“…MCC950, also known as CP-456773 or CRID3 ( Guzova et al., 2019 ; Kuwar et al., 2019 ), is widely known as the most potent and specific NLRP3 inhibitor ( Dai et al., 2021 ). It is often used as a positive control to compare the efficacy of novel NLRP3 inhibitors; for instance, the discovery of nitrostitu-quinazolin-4 (3H)-one 2 K to inhibit the activation of NLRP3 inflammatory body by occupying the ATP-binding site of NLRP3 protein ( Abdullaha et al., 2019 ).…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations